Effects of an Olive By-Product Called Pâté on Cardiovascular Risk Factors. (3rd October 2021) - Dinu, Monica; Pagliai, Giuditta; Scavone, Francesca; Bellumori, Maria; Cecchi, Lorenzo; Nediani, Chiara; Maggini, Niccolò; Sofi, Francesco; Giovannelli, Lisa; Mulinacci, Nadia
Abstract: Background: The nutraceutical effects of Olea europaea L. products are mainly due to phenolic compounds. During olive milling, most of the total phenols remain in the process by-products. Aim: We aimed to evaluate the effects of a specific by-product of olive oil called "pâté" (OlP) administered as tablets, on cardiovascular and metabolic risk factors. Methods: The study was a crossover trial with 2 intervention periods. Nineteen participants (mean age: 38 years) took 4 tablets/day of either olive pâté (corresponding to 30 mg/day of hydroxytyrosol) or placebo for 2 months followed by a 2-month washout and another 2 months of crossed over treatment. Results: After the intervention with pâté, participants showed a statistically significant reduction in plasma levels of total cholesterol (–10.8 mg/dL), LDL cholesterol (–10.8 mg/dL) and urea (–4.1 mg/dL), and a significant increase in calcium levels (+0.3 mg/dL). Leukocyte response to exogenous oxidative stress was significantly reduced (–12.8%) and levels of the antioxidant transcription factor Nrf-2 increased by 88.9%. Plasma levels of the pro-inflammatory protein MCP-1 were significantly reduced (–9.0 pg/mL). Conclusion: In conclusion, the intake of OlP showed positive effects on several cardiovascular risk factors, demonstrating the nutraceutical potential of a widely available but, to date, underestimated olive oil by-product.